MENINGKATKAN KREATIVITAS ANAK USIA 4-5 TAHUN MELALUI KEGIATAN MENCETAK DARI BAHAN ALAM (Penelitian Tindakan Kelas di PAUD Negeri Pembina Terpadu Pandeglang-Banten) - Vika Arliati (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
Creativity is an individual ability in the form of ideas, methods, processes, or new products that are inofatif and imaginative. One of the activities that can improve the creativity of children is the activity of printing from natural materials. The print activity is chosen because in addition to exciting and fun the child can create new ideas that the child wants. This study aims to improve the creativity of children aged 4-5 years. The research method used is Classroom Action Research. The subjects consisted of 14 children. Technique Data collection is done by observation, interview, field notes, and documentation. Implementation of the research is done with 2 cycles that cycle I consists of 8 times action and in cycle II consists of 2 actions. The results of this study show the creativity of children develop optimally, because the learning process begins by making RKH, perform actions and observations in each cycle, and carry out reflections to improve activities that are considered still less good. This is evidenced by the results of the percentage of children’s creativity, namely: 1) At the pre-study of 19%, 20 After the children were given action in the cycle I increased the creativity of children by 36%, 3) In the second cycle obtained by 77%. Thus, children’s creativity can be said to increase and be on a very good growth. it can be concluded, that by using the activities of printing from natural materials can enhance the creativity of children aged 4-5 years in PAUD Integrated Pandeglang Pembina Country.